Drugs to support smoking cessation in UK general practice: are evidence based guidelines being followed?. Issue 4 (2nd August 2006) - Wilson, A; Sinfield, P; Rodgers, S; Hammersley, V; Coleman, T
Abstract : Background: Prescribing drugs to support smoking cessation is one of the most cost effective interventions in primary care, but there is evidence they are underused. Little is known about how far guidelines have been adopted. Aims: To examine the context in which nicotine replacement therapy (NRT) and bupropion are prescribed in UK general practice and whether guidelines are being followed. Design: Patient questionnaire survey. Setting: Twenty five general practices from the Trent Focus Collaborative Research Network in South Yorkshire and East Midlands, UK. Methods: Participating practices posted a questionnaire to up to 40 patients prescribed NRT and bupropion respectively in the previous 3–9 months. Results: The response rate for people prescribed NRT was 44.7% (323/723) and for bupropion 42.5% (77/181). Patients reported initiating the prescription request in 258 cases (65%), whereas GPs were reported as suggesting it in 49 (12%), smoking cessation services (SCS) in 38 (10%), and practice nurses in 36 (9%). Of those who could recall the content of the consultation in which NRT or bupropion was prescribed, 191 (79%) reported receiving advice on treatment use and 209 (68%) were encouraged to set a quit date. Follow up by SCS was recommended to 186 (64%) and practice follow up was offered to 212 (63%), but 41 (15%) reported no offer of follow up support. Conclusions: The majority of patients reported receiving advice and follow up in line with guidelines. However, relatively few prescriptions were suggested by GPs or practice nurses and, in a significant minority of cases, neither follow up by the practice nor additional support from SCS was recommended. More active implementation of guidelines could increase the impact of general practice on the prevalence of smoking.